Evaluasi Usability Terhadap Antarmuka Pengguna Sistem Informasi Kesehatan Menggunakan Heuristic Walkthrough: Studi Kasus pada Sistem Informasi Kesehatan Primer Poliklinik Pabrik Gula Kebonagung Malang Indonesia - Radhy Muhammad Ampera; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
SIKP-KA is a web based electronic health record that contains modules used by health professionals at Kebonagung Sugar Factory Health Clinic. Electronic health records are used because of a variety of benefits such as: more reliable prescriptions, faster access to patient records and a reduction in cost due to a decrease in the amount of paper documents. For these benefits to be achieved, the usability of an electronic health record must enable users to achieve desired results. To discover the usability problems of SIKP-KA, a usability evaluation is requried. Using the heuristic walkthrough method which consists of a cognitive walkthrough and a heuristic evaluation, the usability problems of SIKP-KA can be discovered. In this research, the evaluation using a cognitive walkthrough was conducted by subject matter experts and usability experts and discovered in which steps of the tasks within SIKP-KA were there usability problems. Whereas the evaluation using a heuristic evaluation was conducted by only usability experts and found usability problems by comparing SIKP-KA to a set of predetermined heuristics, severity ratings were also given to each problem found. After the evaluation was completed, the cognitive walkthrough found 44 problems of which 54% were also found in the heuristic evaluation. Whereas the heuristic evaluation found 20 problems, of which the heuristic with the most amount of problems was H-3 (User control and freedom) with 35% of all discovered heuristic evaluation problems.